New generic records of grasses from Tripura, India - Ghosh, Sampa; Bhattacharyya, Debjyoti (Plant Science Today, 2020)
Five species of grasses (Gramineae, nom. alt. Poaceae) namely Eriochloa procera (Retz.) C. E. Hubb., Heteropogon contortus (L.) P. Beauv. ex Roem. & Schult., Perotis indica (L.) Kuntze, Phalaris minor Retz. and Pseudoraphis brunoniana (Griff.) Pilg. are reported here for the first time from Tripura, India. Literature review revealed that all are the first representative species under respective genus from the state which eventually proclaim five new generic records of grasses from the state of Tripura. Brief description with illustration, habitat, phenology of all the species are presented. Field photographs are also given for facilitating easy identification.